Mastering the SAS DS2 procedure : advanced data wrangling techniques - Jordan, Mark (SAS Institute, 2016)
With examples used systematically throughout, this book provides an extremely concise introduction to not only the syntax of the SAS DS2 language but, more importantly, to the objectives of the language. --